Environmental factors related to the vegetational variation of a natural grassland - Pillar, Valerio De Patta; Jacques, Aino Victor Avila; Boldrini, Ilsi I. (Pesquisa Agropecuaria Brasileira, 1992)
In this work the relationships between vegetation structure and environmental factors were studied. In a 30-ha natural grassland, 60 quadrats (0,25 m2) located on topographic gradients at each change in vegetation, were evaluated in terms of environmental factors and cover-abundance of species. Identification of community and species groups were done by using classification and ordination techniques. The community type Eleocharis-Centella occurs at lower and moister sites, Desmodium Axonopus-Paspalum and Baccharis-Andropogon occur at medium moisture, and Facelis-Paspalum, Eryngium and Arista-Borreria-Paspalum occur at dryer sites. In addition, dispersion profiles of species in relation to environmental factors were analysed. Hypotheses on vegetation succession due to changes in the environmental conditions were generated.